A Study on Identification of Consumer Groups buying at Apparel Retail Store: A Cluster Analysis - M K M, Manikandan (Ushus Journal of Business Management, 2013)
The Indian Retail Industry is growing at such a fast rate that many foreign retailers want to capitalize on the growth momentum and the opportunity offered by the growing buying power of middle class. Many retailers are already present in Indian retail landscape and they are finding it difficult to run the business profitably. Not many India specific retail research has been carried out so far. Of late many researchers are coming up with studies that focus on India specific retailing. This study tries to study the type of customers who are visiting the apparel retailers and tries to group them based on certain parameters like their occupation, continued patronage and age. Cluster analysis is used as a statistical tool to group the sample into various groups. The result indicates the existence of four types of customer groups for the apparel retailing stores